Financial Literacy and the Moderating Effects of Personality Traits on Financial Planning in Malaysia - Stellia, Djapri; Brahmana, Rayenda Khresna; Puah, Chin Hong (Universiti Malaysia Sarawak, (UNIMAS), 2019)
Unlike previous financial literacy – financial planning research, we test the moderation effect of personality traits using Big-5 traits on the relationship. We collect 409 respondents and test the hypothesis using Structural Equation Model. This research offers several appealing features for an analysis of financial literacy and financial planning. Psychological factors are added as the moderating variable on that association. This study explores the relationship between psychological factors and financial planning from an empirical perspectives. Specifically, by conducting survey in Malaysia, this research analyzes the influence of psychological factors on financial planning at the individual level focusing on the demographic profiles and financial literacy level. Personality traits are classified according to the ‘Big Five’ taxonomy: openness to experience, conscientiousness, extraversion, agreeableness and neuroticism. Conscientiousness, extraversion and neuroticism exert relatively large influences on financial planning in terms of the levels of financial literacy held by each individual. In contrast, openness to experience and agreeableness appear to be unimportant in influencing financial planning. The findings also suggest that personality traits have different moderating effects with financial literacy. For example, only neuroticism trait is found to have small moderating effect with financial literacy towards financial planning, where the other four traits have no moderating effect at all.